Innovation of moringa leaf (Moringa oleifera) body scrub for sustainable beauty product development [Inovasi body scrub daun kelor (Moringa oleifera) untuk pengembangan produk kecantikan berkelanjutan] - Jinan, Riadhil; Susanna, S; Alfayet, Rifal; Rauzah, R; Ikhwan, Ridha Sujanna; Ramadhani, Reskina; Nirabela, Reni; Alfiza, Rini; Kasyuanti, Rima; Sulastri, Rini; Delfinna, Rila (Buletin Pengabdian, 2025)
The popularity of natural ingredient-based cosmetics is increasing in tandem with growing consumer awareness of the long-term effects of chemicals on skin and the environment. This activity focuses on the utilization of moringa leaves (Moringa oleifera) as a raw material for skincare products, specifically body scrub, in Ie Masen Village, Ulee Kareng Sub-District, Banda Aceh. Moringa leaves are renowned for their high antioxidant content and nutritional value, positioning them as potential agents for effective anti-aging and skincare. The objective of this activity is to enhance community knowledge and engagement regarding the use of moringa leaves as a raw material for skincare products, particularly body scrub. The research methodology includes observation, interviews, and discussions with local communities. This activity encompassed socialization, product trials, and evaluation of a body scrub that combines moringa leaves, rice flour, turmeric, and lemon. The findings indicated that the moringa leaf body scrub can improve community awareness of natural ingredient utilization and has the potential to become a micro, small, and medium-sized enterprise (MSME). This activity was positively received by the community, , and the evaluation results demonstrated that this product is effective in exfoliation and skincare. In conclusion, this activity contributes to the development of natural beauty products that support sustainability and skin health.